Analysis on the factors that influence students’ perception towards whistleblowing intention / Khamisah Abd Manaf - Abd Manaf, Khamisah (2022)
Whistleblowing is a disclosure by a member of organisation of any misconduct perpetrated by the management. This noble deed is an effective tool to deter misconducts and hence it is a duty of all parties who stumbled upon such incidences to report to those who can execute actions. This investigation glares at students’ perceptions of intention to whistle blow. This study was conducted with the respondents within the Faculty of Business and Management of the Universiti Teknologi MARA, Kelantan campus as numerous as 300 students by conducting a survey conveyance. The findings of this study are students' perceptions which develop from three variables that become independent variables, namely social influence (SI), attitudes towards behaviour (ATB) and perceptions of organizational support (OS) have a positive influence on student intentions to blow the whistle. This study is anticipated to be an additional information regarding students' discernments in observing the whistleblowing activities. An understanding of the views of students towards whistleblowing and the factors driving their intentions should be useful to organisations that may use these students upon graduation.